A comparative study of wave‐current interactions over the eastern Canadian shelf under severe weather conditions using a coupled wave‐circulation model. Issue 7 (31st July 2016) - Wang, Pengcheng; Sheng, Jinyu
Abstract: A coupled wave‐circulation model is used to examine interactions between surface gravity waves and ocean currents over the eastern Canadian shelf and adjacent deep waters during three severe weather events. The simulated significant wave heights (SWHs) and peak wave periods reveal the importance of wave‐current interactions (WCI) during and after the storm. In two fast‐moving hurricane cases, the maximum SWHs are reduced by more than 11% on the right‐hand side of the storm track and increased by about 5% on the left‐hand side due to different WCI mechanisms on waves on two sides of the track. The dominate mechanisms of the WCI on waves include the current‐induced modification of wind energy input to the wave generation, and current‐induced wave advection and refraction. In the slow‐moving winter storm case, the effect of WCI decreases the maximum SWHs on both sides of the storm track due to different results of the current‐induced wave advection, which is affected greatly by the storm translation speed. The simulated sea surface temperature (SST) cooling induced by hurricanes and SST warming induced by the winter storm are also enhanced (up to 1.2°C) by the WCI mechanisms on circulation and hydrography. The 3D wave forces can affect water columns up to 200 m in all three storm cases. By comparison, the effect of breaking wave‐induced mixing in the ocean upper layer is more important under strong stratification conditions in two hurricane cases than under weak stratification conditions in the winter storm case. Key Points: A comparative study of wave‐current interactions during three storms Application of a coupled model based on a 3D circulation model and a third‐generation wave model Examining the role of the storm translation speed in wave‐current interactions